FREDERICK H. HARTMANN AND THE RELATIONS OF NATIONS - Peruana de Derecho Internacional, Sociedad (2020)
Frederick Hartmann was born in New York in 1922 and died in 2015 at the age of 93.He graduated from the University of California at Berkeley, he joined the US Navy in theaccelerated program during World War II and took part in nine invasions including that ofPalau, Leyte, Linguyen, Gulf and Okinawa and was award with 7 battle stars.In 1946, he enrolled in the Princeton University Graduate School program, obtaining aPhD in Politics in 1949. He was professor at the University of Florida in 1948 where he wasquickly promoted to associate professor and then to full professor. Hartmann commanded adivision of the Naval Reserve in Gainesville, Florida and was promoted to Captain in 1966.That year he accepted a new position created at the United States Naval War College inNewport, Rhode Island, where he served for 20 years as Professor of Political Science and wasthe senior adviser to nine presidents of the Naval War College. His prolific literary productionled him to write fifteen books, all of them very well known, including his most important ones:The Relations of Nations and The Conservation of Enemies.This author as an Alum of the US Naval War College is honored to attempt to revive hislegacy, in this short article, for the prestigious Journal of the Peruvian Society of InternationalLaw, in which I try to revisit his most famous book: The Relations of Nations written in 1957with six editions and translated into many languages, being used in international businessschools, war schools, and foreign policy schools in many countries. The central theme of thisarticle is the focus of the curriculum of the US Naval War College which are the internationalrelations and the politics and strategy in the development of nations.